Focal nodular hyperplasia of the liver: Two clinical case reports with an atypical presentation - Borges, Sérgio (2007)
Focal nodular hyperplasia of the liver (FNH) usually presents as a solitary, benign, asymptomatic lesion in the female sex. The authors present two cases of FNH. A 27-year-old man presented with a slight liver enzyme increase on routine blood analysis. Ultrasonography, CT and MRI were performed and showed a solitary mass in the left hepatic lobe, characteristic of FNH. The patient was followed up over seven years. He became progressively symptomatic with epigastric pain and postprandial fullness and underwent surgical resection which resulted in symptomatic relief. The other case is a 42-year-old female, who had been taking oral contraceptives, with three hepatic masses seen ultrasonically on a liver scan performed to investigate unspecific abdominal pain. MRI confirmed the diagnosis of FNH. The patient has been followed-up for two years and remains asymptomatic. The authors decided to present these cases because of their atypical features. In the first one: it is unusual to make a diagnosis of FNH in male patients and cases are rarely symptomatic with the need for surgical resection. In the second one: multiple lesions are rare. The controversial question of the association between oral contraceptives and FNH is raised.